La convención internacional de los derechos del niño ante el reto de la realidad - Ruíz-Giménez, Joaquín (Revista Española de Pedagogía, 2018)
The paper is divided in four parts. In the first one, the author begins showing the situation of children in the world which presents the need for a new international agreement, a stronger link among ourselves such as the International Covenant. In the next part, the author describes the content of the Covenant. He highlights the acknowledgement ofprocedural and penal rights for children and the requirement to establish a worldwide child rights committee. In the third part, the problems and possibilities involved in applying the covenant are analyzed. On the side, the author takes into account the high number ofratifications in a briefperiod oftime and the specific Program of objectives and strategies developped in the World Meeting celebrated in 1990. The big disappointment is that an economic program has not been approved. Whithout it, the Covenant will not be useful. The paper finishes by showing sorne ways to close the distance between the present reality for the world's children and the ideals of the Covenant.
Keywords: derecho del niño; pacto internacional de derechos; Revista Española de Pedagogía